2020
DOI: 10.3390/mi11121029
|View full text |Cite
|
Sign up to set email alerts
|

A Method to Determine the Minimum Chip Thickness during Longitudinal Turning

Abstract: Micromachining, which is used for various industrial purposes, requires the depth of cut and feed to be expressed in micrometers. Appropriate stock allowance and cutting conditions need to be selected to ensure that excess material is removed in the form of chips. To calculate the allowance, it is essential to take into account the tool nose radius, as this cutting parameter affects the minimum chip thickness. Theoretical and numerical studies on the topic predominate over experimental ones. This article descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…The material was steel 1.2709. As the condition of the cutting edge and its sharpness are some of the key factors in cutting operations [29,30], the analysis of the additively manufactured tool focused on determining its dimensional and geometric accuracy, the cutting edge radius and the surface quality.…”
Section: Introductionmentioning
confidence: 99%
“…The material was steel 1.2709. As the condition of the cutting edge and its sharpness are some of the key factors in cutting operations [29,30], the analysis of the additively manufactured tool focused on determining its dimensional and geometric accuracy, the cutting edge radius and the surface quality.…”
Section: Introductionmentioning
confidence: 99%
“…In the lists created by the authors of previous works, the factors influencing shaped surfaces have been selected and divided into main groups related to [ 7 , 8 ] cutting tool, machining parameters, properties of the machined material, and phenomena accompanying the machining [ 9 , 10 ]. Phenomena involved in machining that affect the surface quality are: machining forces, chip forming and detachment, friction in the machining zone, vibration acceleration, displacement, built-up edge, and temperature distribution and flow [ 11 ]. In many works, models for predicting the roughness values of Ra and Rt are often found, as these are the most common industry requirements for roughness for manufactured parts.…”
Section: Introductionmentioning
confidence: 99%
“…Dib et al [17] determined the minimum uncut chip thickness by means of cutting forces from the dynamometer. Skrzyniarz et al [18] determined the minimum uncut chip thickness of micro turning from a surface profile 2 of 15 obtained with a contact profilometer. Vogler et al [19] found the minimum uncut chip thickness values in micro-milling ferrite and pearlite materials through finite element simulations.…”
Section: Introductionmentioning
confidence: 99%